Effect of Helicobacter pylorieradication on chronic gastritis during omeprazole therapy. Issue 5 (1st May 2000) - Schenk, B E; Kuipers, E J; Nelis, G F; Bloemena, E; Thijs, J C; Snel, P; Luckers, A E G; Klinkenberg-Knol, E C; Festen, H P M; Viergever, P P; Lindeman, J; Meuwissen, S G M
Abstract : BACKGROUND: We have previously observed that profound acid suppressive therapy in Helicobacter pylori positive patients with gastro-oesophageal reflux disease is associated with increased corpus inflammation and accelerated development of atrophic gastritis. AIM: To investigate if H pylori eradication at the start of acid suppressive therapy prevents the development of these histological changes. PATIENTS/METHODS: In a prospective randomised case control study, patients with reflux oesophagitis were treated with omeprazole 40 mg once daily for 12 months. H pylori positive patients were randomised to additional double blind treatment with omeprazole 20 mg, amoxicillin 1000 mg and clarithromycin 500 mg twice daily or placebo for one week. Biopsy sampling for histology, scored according to the updated Sydney classification, and culture were performed at baseline, and at three and 12 months. RESULTS: In the persistently H pylori positive group (n=24), active inflammation increased in the corpus and decreased in the antrum during therapy (p=0.032 and p=0.002, respectively). In contrast, in the H pylori positive group that became H pylori negative as a result of treatment (n=33), active and chronic inflammation in both the corpus and antrum decreased (p⩽0.0001). The decrease in active and chronic inflammation in the corpus differed significantly compared with the persistently H pylori positive group (both p=0.001). For atrophy scores, no significant differences were observed between H pylori eradicated and persistently H pylori positive patients within one year of follow up. No changes were observed in the H pylori negative control group (n=26). CONCLUSIONS: H pylori eradication prevents the increase in corpus gastritis associated with profound acid suppressive therapy. Longer follow up is needed to determine if H pylori eradication prevents the development of atrophic gastritis.